(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2006)
The Author analyzes the most recent gas and oil nationalization in Bolivia. This expropriation of foreign companies did not happen for the first time ever in Bolivia's history. Its legitimacy under the standpoint of International Law is connected to the payment of compensation.